2005
DOI: 10.1002/mrm.20526
|View full text |Cite
|
Sign up to set email alerts
|

In‐plane velocity encoding with coherent steady‐state imaging

Abstract: Standard phase-contrast flow quantification (PC-FQ) using radiofrequency (RF) spoiled steady-state (SS) incoherent gradient-echo sequences have a relatively low signal-to-noise ratio (SNR). Unspoiled SS coherent (SSC) gradient-echo sequences have a higher intrinsic SNR and are T 2 /T 1 weighted so that blood has a relatively large signal compared to other tissues. An SSC sequence that was modified to allow in-plane velocity encoding is presented. Velocity encoding was achieved by inverting the readout gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Given this constraint, the development of a new PC-MRI sequence that can improve the temporal resolution while maintaining data acquisition time would be desirable. While higher temporal resolution can be achieved by alternate spiral acquisition (16) or the use of steady-state velocity encoding sequences (17), there is typically a compromise on spatial resolution or image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Given this constraint, the development of a new PC-MRI sequence that can improve the temporal resolution while maintaining data acquisition time would be desirable. While higher temporal resolution can be achieved by alternate spiral acquisition (16) or the use of steady-state velocity encoding sequences (17), there is typically a compromise on spatial resolution or image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it provides a unique T2/T1 contrast that can be particularly beneficial in certain applications (Hargreaves et al, 2003; Nayak et al, 2005). However, with a few exceptions such as flow imaging (Overall et al, 2002; Markl et al, 2003; Grinstead and Sinha, 2005), neuronal current measurement (Buracas et al, 2008) and bSSFP fMRI (Miller et al, 2003; Scheffler et al, 2001) where strong phase contrast has been demonstrated (Lee et al, 2007), most of the bSSFP studies have utilized only the image magnitude and ignored the image phase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, particle paths can be superimposed instead of vector field maps. These paths were calculated from the phase-contrast flow quan-tification data using simple kinematic equations of motion as described elsewhere [7,8] …”
Section: Grinstead Et Almentioning
confidence: 99%
“…Information in the DICOM header allowed the velocity encoding values, encoding direction, temporal resolution, cine frame number, pixel size, and so on to be imported automatically along with the pixel data. The visualization tools we used and developed were previously described in more detail [6,7]. Briefly, considering an axial slice, the through-plane velocity data (superior-inferior) are plotted as contour maps with isocontour lines separating regions of differing velocity ranges.…”
mentioning
confidence: 99%